Pengaruh Parkir pada Badan Jalan terhadap Kinerja Ruas Jalan MT Haryono di Kota Balikpapan - Octavia, Annisa; Maslina, Maslina; Devi, Suheriah Mulia (Jurnal Talenta Sipil, 2024)
This study aims to examine the impact of on-street parking on the performance of MT Haryono Road in Balikpapan City. The research employs a qualitative descriptive method. The analysis reveals that the presence of on-street parking significantly affects road performance. On Tuesday, the day with the highest traffic volume, the degree of saturation during peak afternoon hours reached 0.89 with on-street parking and decreased to 0.85 when parking was moved off-street. The Level of Service (LOS) on Monday and Tuesday was categorized as E, indicating congested traffic conditions with very high side friction. The LOS improved to category C on Wednesday and Sunday, indicating unstable traffic flow with limited speeds and considerable side friction. The LOS was categorized as D on Thursday, Friday, and Saturday, indicating saturated traffic flow with starting low speeds and high side friction. The worst traffic conditions occurred on Tuesday, April 2, 2024, with a LOS of E and a degree of saturation of 0.89. Conversely, the best traffic conditions occurred on Sunday, April 7, 2024, with a LOS of C and a degree of saturation of 0.62. The study's findings highlight the importance of parking management to enhance road performance in urban areas.